IMPLEMENTASI MODEL NEWSVENDOR DENGAN KAPASITAS REAKTIF DI PT. XYZ - Sumargo, Seto; Damayanti, Dida Diah (KAIZEN : Management Systems & Industrial Engineering Journal, 2023)
PT. XYZ is a company that sells fashion products. The main business process of the company is designing, marketing, and selling fashion products. The fashion products sold by the company are clothes, footwear, bags, and other accessories. The selection of footwear products is based on the trend of increasing demand from year to year. This study aims to determine the number of footwears ordered for the limited category that will be sold in the next sales period. The lead time for procuring footwear is 3 months, special lead time for second order is 1 month and the selling period for products at normal prices is 6 months. The results of calculations using the newsvendor model with reactive capacity obtained the number of first order is 486 pairs and the number of second order is 69 pairs. With the second order, the expected loss of sales does not exist. The expected leftover with reactive capacity decreased by 82.32% and became 32 pairs. Performance measurements newsvendor model with reactive capacity obtained the expected profit is IDR 88,374,150 or 11.52% more than single order. Based on these measurements, companies are advised to implement the newsvendor model with reactive capacity to increase expected profits. Keywords: inventory, newsvendor model, reactive capacity ABSTRAK PT. XYZ adalah perusahaan yang menjual produk fashion. Proses bisnis utama dari perusahaan adalah mendesain, memasarkan dan menjual produk fashion. Produk fashion yang dijual oleh perusahaan adalah baju, alas kaki, tas dan aksesoris lainnya. Pemilihan produk alas kaki berdasarkan tren permintaan yang meningkat dari tahun ke tahun. Penelitian ini bertujuan untuk menentukan jumlah alas kaki yang dipesan untuk kategori terbatas yang akan dijual pada periode penjualan berikutnya. Lead time untuk pengadaan alas kaki adalah 3 bulan, lead time khusus pada pesanan ke 2 adalah 1 bulan dan lama periode penjualan produk dengan harga normal adalah 6 bulan. Hasil perhitungan menggunakan model newsvendor dengan kapasitas reaktif diperoleh jumlah pesanan pertama sebanyak 486 pasang dan jumlah pesanan kedua sebanyak 69 pasang. Dengan adanya pesanan kedua maka kehilangan penjualan yang diharapkan tidak ada. Sisa barang yang diharapkan dengan kapasitas reaktif menurun 82,32% menjadi 32 pasang. Pengukuran kinerja dengan kapasitas reaktif diperoleh keuntungan yang diharapkan sebesar Rp88.374.150 atau 11,52% lebih banyak daripada dengan satu kali pesanan. Berdasarkan pengukuran tersebut perusahaan disarankan untuk mengimplementasi model newsvendor dengan kapasitas reaktif untuk meningkatkan keuntungan yang diharapkan.. Kata kunci:  kapasitas reaktif, model newsvendor, persediaan